RNA-seq reveals cooperative metabolic interactions between two termite-gut spirochete species in co-culture - Rosenthal, Adam Z; Matson, Eric G; Eldar, Avigdor; Leadbetter, Jared R (The ISME Journal, 2011)
The hindguts of wood-feeding termites typically contain hundreds of microbial species. Together with their insect host, these gut microbes degrade lignocellulose into usable catabolites. Although past research revealed many facets of the stepwise flow of metabolites in this scheme, not much is known about the breadth of interactions occurring between termite-gut microbes. Most of these microbes are thought to depend on, and to have co-speciated with, their host and each other for millions of years. In this study, we explored the interactions of two spirochetes previously isolated from the very same termite species. As hydrogen (H 2 ) is the central free intermediate in termite-gut lignocellulose digestion, we focused on interactions between two closely related termite-gut spirochetes possessing complementary H 2 physiologies: one produces H 2 , while the other consumes it. In vitro , these two Treponema species markedly enhanced each other's growth. RNA sequencing resolved the transcriptomes of these two closely related organisms, revealing that co-cultivation causes comprehensive changes in global gene expression. The expression of well over a 100 genes in each species was changed >twofold, with over a dozen changed >10-fold. Several changes implicating synergistic cross-feeding of known metabolites were validated in vitro . Additionally, certain activities beneficial to the host were preferentially expressed during consortial growth. However, the majority of changes in gene expression are not yet understandable, but indicate a broad, comprehensive and mutualistic interaction between these closely related, co-resident gut symbionts. The results suggest that staggeringly intricate networks of metabolic and gene interactions drive lignocellulose degradation and co-evolution of termite gut microbiota.